Expression Virus-Like Particles (VLPs) at Geomembrane and Concret in Asian Pacific Shrimp Culture (Litopenaeus vannamei) - Hidayah, Venny Nur; Musa, Muhammad; Kilawati, Yuni (Graduate School, Universitas Brawijaya, 2021)
Asian Pacific Shrimp is an invertebrate that the most culture in aquaculture. But the high demand for shrimp makes farmers cultivate a high density. There are several ways to increase the density of shrimp culture, usually called geomembrane plastic and concrete ponds. The ponds are located in the Laboratory of Brackishwater and Seawater Fisheries, Probolinggo and Lucky Windu, Situbondo. Day of Culture (DOC) on Laboratory of Brackishwater and Seawater Fisheries in Probolinggo pond is 85 days both, while in Lucky Windu Situbondo is 81 days on pond 2, and pondÂ 3B 133 days. The study aimed to evaluate correlations of VLPs towards geomembrane and concrete ponds. The research method has two observations: 1. Periodic observations; nitrite, ammonium, and shrimp were observed; 2. Last observation; sampling water for analysis VLPs was observed. Data of sampling water in the different ponds were then analyzed using Pearson correlation analysis to look for the level of tightness and direction of the relationship. The results have obtained that geomembrane VLPs and concrete VLPs has a very strong relationship, while the type of geomembrane and concrete was close to 1 > 0.5 and the result is 0.90, 0.96, 0.69, and 0.82. Water quality showed pH 8.1 at geomembrane, nitrite 0.2mg.L-1 at geomembrane, and ammonium of 0.44 mg.L-1 at concrete. The pond area in geomembrane pond 1 and 2 was 1600 m2, meanwhile in concrete both is 4300 m2, which mean in concrete ponds more the existence of VLPs is because due to the different pond area factors and indicates from detections of WSSV that the result was positive that makes environment factor in abundances VLPs. But VLPs have no effect on the growth of shrimp vaname during the cultivated process.Keywords: Asian Shrimp Pasific (L. vannamei), Virus-Like Particles (VLPs), Water Quality, and WSSV.